International Security in the Modern World - Salmon, Trevor C. author. aut Link
X, 241 p.
Keywords: Despite the dramatic changes in the international environment since 1989, it remains the case that force, and the threat of force, retain utility. The volume deals with the nature of security, international conflict and co-operation, deterrence, crisis management and prevention, arms control and disarmament, insurgency and low intensity conflict, Third World security, alliances and the role of land, air and naval power. The book takes a predominantly traditional approach, but also introduces students to other perspectives and approaches relating to security and to the security of the Third World.